PENGUKURAN KINERJA RANTAI PASOK BALIK: STUDI KASUS PERUSAHAAN DAUR ULANG ALAT KOMUNIKASI X - Maulida Boru Butar Butar; Stephanus Liwun Bera Liwun (Jurnal Teknik dan Science, 2022)
The supply chain performance, as measured by observing the product return process that occurs at company X, will be presented in this paper. Product return is one of the things that encourages the use of a reverse supply chain in a company. The company must handle returned products from end users so that the returned products received can be profitable. The existing general model is used to examine the possibility of re-manufacturing processes in company X's existing reverse supply chain. The process model of the re-product is investigated and observed. Case studies on small and medium enterprises engaged in recycling electronic products already have a back supply chain process. A general model of the return supply chain at company X will be created, and a mathematical model based on the general model will be proposed to evaluate the performance of the return supply chain. The costs for product returns, when low and high, will be compared as a reference for the company. With the existence of a supply chain model of the processes that return products go through, companies can begin to measure the performance of the supply chain processes and evaluate this process as a way to gain benefits for the company.